Low carbon binder preparation from slag-red mud activated by MSWI fly ash-carbide slag: Hydration characteristics and heavy metals' solidification behavior. (10th November 2022) - Bai, Yanying; Guo, Weichao; Zhang, Yangyang; Xue, Caihong; Xu, Zehua; Gao, Qingyu; Xiao, Chang; Zhao, Qingxin
Abstract: Municipal solid waste incineration fly ash (MSWIFA) is hazardous, which safe disposal is a challenge. This study successfully prepared binder using MSWIFA and carbide slag (CS) as solid waste alkaline activators, stimulating the activity of red mud (RM) and ground granulated blast-furnace slag (GGBS). The properties and evolution mechanism of the binder were comprehensively evaluated in terms of compressive strength, fluidity, heavy metal leaching concentration, chloride ions' curing rate, and micromethods (XRD, SEM, EDS, and FTIR). The results show that CS and MSWIFA provide an alkaline environment for the hydration of RM and GGBS, promoting the formation of hydrated calcium chloroaluminate (HCC), ettringite, C-(A)-S-H gels and hydrotalcite (HT). At a mixing ratio CS: RM: GGBS: MSWIFA = 1:3:3:3, the binder had fluidity of 130 mm, 28 d compressive strength of 24.49 MPa and chloride curing rate over 80%. The environmental pH value mainly controlled the leaching risk of harmful components: its increase dropped the leaching rate of heavy metals. The addition of GGBS improved the structural compactness and buffering resistance of the matrix, effectively reducing the leaching risk of Cr and Zn heavy metals and keeping the leaching concentration of hazardous substances within the limits of national standards. This new binder system can be used to prepare pavement bricks and concrete blocks, mitigating solid waste environmental pressure and saving binder preparation costs. Graphical abstract: Image 1 Highlights: These binders use MSWIFA and CS to replace the traditional chemical activator. The best ratio was obtained with a CS-to-RM-to-GGBS-to-MSWIFA ratio of 1:3:3:3. The new binder has good ability to immobilize heavy metals and chloride ions. The main hydration products are C-(A)-S-H gel, HCC and HT.